Direction dependent strong magnetoelectric coupling in La0.7Ba0.3MnO3 embedded poly(vinylidenefluoride-co-trifluoroethylene) flexible nano-composite films at room temperature. (December 2020) - Koner, Sougata; Deshmukh, Pratik; Khan, Azam Ali; Ahlawat, Anju; Karnal, A.K.; Satapathy, S.
Abstract: Magnetoelectric coupling of La0.7 Ba0.3 MnO3 / poly(vinylidenefluoride-co-trifluoroethylene) nano-composite (0–3) films were studied by varying the volume fraction of La0.7 Ba0.3 MnO3 in polymer matrix for non-poled and electrically poled conditions. The transverse magnetoelectric coupling coefficient (α V 31 ) value is larger compared to α V 33 (logitudinal coupling coeffcient) for composite films. The maximum value of α V 31 is found to be 121.44 mVcm −1 Oe −1 for poled composite films (0.5% La0.7 Ba0.3 MnO3 volume fraction) at 10 kHz. These films generate a self-biased voltage 9.1 mV on application of 25Oe alternating magnetic field (Hac ). The dependence of α V 31 of these films on static magnetic field (Hdc ), Hac and frequency is also reported. Graphical abstract: Image, graphical abstract